High T(3), Low T(4) Serum Levels in Mct8 Deficiency Are Not Caused by Increased Hepatic Conversion through Type I Deiodinase - Wirth, Eva K. (Eur Thyroid J, 2015)
BACKGROUND: The Allan-Herndon-Dudley syndrome is a severe psychomotor retardation accompanied by specific changes in circulating thyroid hormone levels (high T(3), low T(4)). These are caused by mutations in the thyroid hormone transmembrane transport protein monocarboxylate transporter 8 (MCT8). Objective: To test the hypothesis that circulating low T(4) and high T(3) levels are caused by enhanced conversion of T(4) via increased activity of hepatic type I deiodinase (Dio1). METHODS: We crossed mice deficient in Mct8 with mice lacking Dio1 activity in hepatocytes. Translation of the selenoenzyme Dio1 was abrogated by hepatocyte-specific inactivation of selenoprotein biosynthesis. RESULTS: Inactivation of Dio1 activity in the livers of global Mct8-deficient mice does not restore normal circulating thyroid hormone levels. CONCLUSIONS: Our data suggest that although hepatic Dio1 activity is increased in Mct8-deficient mice, it does not cause the observed abnormal circulating thyroid hormone levels. Since global inactivation of Dio1 in Mct8-deficient mice does normalize circulating thyroid hormone levels, the underlying mechanism and relevant tissues involved remain to be elucidated.